Dynamics changes in the number of students attending higher education establishments according to the areas of specialities - Кислицька, І. (Київський національний університет імені Тараса Шевченка, 2017)
Дослідження присвячене аналізу основних тенденцій у сфері вищої освіти України. У роботі проаналізовано динаміку кількості вищих навчальних закладів за 2006-2016 р., виявлено особливості їх територіального розміщення, наведено передумови виявлених змін у чисельності студентів за аналогічний період. Особливий наголос зроблено на напрямах підготовки студентів. Виділено ТОП-5 напрямів в Україні за кількістю прийнятих на навчання студентів у 2010/11 та 2016/17 н. р. Виявлені загальнонаціональні закономірності підтверджено на прикладі Київського університету імені Тараса Шевченка.

The study is devoted to the analysis of the main tendencies in the field of higher education in Ukraine. The paper analyzes the dynamics of the number of higher educational institutions for 2006-2016 and the number of students for the same period. It is determined that the revealed changes, first of all, are due to demographic features (reduction of the general population and population aged 15-19 years, as well as reduction of the birth rate). The features of territorial placement of institutions of higher education are outlined. The unevenness of their placement was revealed. In particular, half of all higher educational institutions are concentrated in five regions of Ukraine (Kyiv, Kharkiv, Dnipropetrovsk, Lviv and Odessa regions), and the smallest number of higher educational institutions operates in the occupied Luhansk region. Special emphasis is placed on the training of students. It was found that in all directions there is a decrease in the number of students, with the highest rate of reduction characteristic of the direction of training “Social Sciences, Business and Law”. It was found that during the period under review, significant changes in the number of students did not take place in such highly specialized areas as “Veterinary Medicine”, “Social Security” and “Agriculture, Forestry and Fisheries and their Processing of Products”. Significant changes were observed in the relevant period of study in such areas as “Military Science” and “Health”. The article also highlights the TOP-5 trends in Ukraine by the number of students admitted to study in 2010/11 and 2016/17 n. р. So, if in 2010/11, Among the entrants, the following specialties were popular: “Social sciences, business and law”, “Engineering”, “Health”, “Humanities and art”, “Education”, then in 2016/17 n. ‒ Management and Administration, Health, Information Technologies, as well as traditional Education and Law. The established national laws are also confirmed by the example of the introductory campaigns of 2008/09 and 2016/17 n. Taras Shevchenko National University of Kyiv. The attempts to justify the revealed tendencies and their main preconditions are determined. It was found that the training of specialists in such areas as “Engineering”, “Architecture”, “Medicine”, “Chemistry” is conducted in higher educational institutions of state ownership, and for institutions of non-state form of ownership, the training of specialists in the field of economics and entrepreneurship, sociological research, law.
Динаміка чисельності студентів вищих навчальних закладів за основними напрямами
Офіційний сайт Державної служби статистики України [Електронний ресурс]. – Режим доступу: http://www.ukrstat.gov.ua/ Офіційний сайт ІС «Конкурс» Міністерства освіти та науки України [Електронний ресурс]. – Режим доступу: http://www.vstup.info/
Keywords: заклад вищої освіти; напрям підготовки; рівень акредитації; навчальний рік; Київський національний університет імені Тараса Шевченка; institution of higher education; specialty; level of accreditation; academic year; Taras Shevchenko National University of Kyiv